Seasonal patterns of mercury bioaccumulation in lobsters (Homarus americanus) from Maine - Dan Stoicov; Carolina A. Bonin; Andre J. van Wijnen; Eric A. Lewallen (Academia Biology)
Mercury (Hg) pollutes marine ecosystems and accumulates in benthic species. This ecological case study investigated the temporal accumulation of Hg in American lobster (Homarus americanus; H. Milne Edwards, 1837) from coastal Maine (Casco Bay, ME, USA). We analyzed total Hg levels in legal-sized lobsters (carapace length: 8.255–12.5 cm; n = 34) collected during the early (May–July 1) or late (July 15–October) recreational harvest seasons. Morphometric data show that body size correlates with body weight (R2 = 0.76; p < 0.001), and average body sizes were similar in early and late seasons. The average chelipod size was ~7% larger in male lobsters (p < 0.02), reflecting sexual dimorphism. Hg levels in select tissues from boiled lobsters were analyzed using atomic absorption spectroscopy. Hg in ambient water was undetectable, indicating that Hg in tissues reflects bioaccumulation. Hg content correlated with the lengths (cm) and weights (g) of cephalothorax, carapace, chelipod, and hepatopancreas in both male and female lobsters. Total Hg levels in most tissues were within safe and acceptable limits for human consumption (<0.2 ppm). Compared to late-season lobsters, early-season lobsters had significantly higher Hg levels in tail (~55% increase; 0.130 ppm vs. 0.084 ppm; p < 0.05) and hepatopancreas tissues (~29% increase; 0.099 ppm vs. 0.077 ppm; p < 0.05), suggesting that seasonal factors influence Hg content (e.g., spring river runoff, lobster migration, inert biological cycles). Observed seasonal fluctuations in lobster Hg levels may inform future strategies for mitigating pollution in coastal marine ecosystems.